1980
DOI: 10.1002/pol.1980.180180512
|View full text |Cite
|
Sign up to set email alerts
|

Structure of glassy polymers. VII. Small‐angle X‐ray scattering from epoxy resins

Abstract: SynopsisThe small-angle x-ray scattering (SAXS) from an Epon 812 and two Epon 828 (one amine-cured and one anhydride-cured) epoxy resins has been measured using a Bonse-Hart system. The data cover the angular range (219) between 20 sec and 60 min. After correction for absorption, background and vertical beam divergence, they have been placed on an absolute basis by comparison with the scattering from a previously studied polycarbonate sample. The corrected absolute intensity decreases strongly with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Whilst small angle neutron or x-ray scattering studies can be found to support resin heterogeneity, the link between nanoscale morphological features and chemical heterogeneity has not been established. 34,35 were bar coated in the same manner from 5 % w/w solutions in toluene (Fisher Scientific, >99%) and then cryogenically fractured prior to analysis.…”
Section: Insights Into Epoxy Network Nanostructural Heterogeneity Usimentioning
confidence: 99%
“…Whilst small angle neutron or x-ray scattering studies can be found to support resin heterogeneity, the link between nanoscale morphological features and chemical heterogeneity has not been established. 34,35 were bar coated in the same manner from 5 % w/w solutions in toluene (Fisher Scientific, >99%) and then cryogenically fractured prior to analysis.…”
Section: Insights Into Epoxy Network Nanostructural Heterogeneity Usimentioning
confidence: 99%
“…However, there are only a few SANS and SAXS studies addressing the nodular structures as compared to the number of SEM and TEM studies on the inhomogeneity. 2,[13][14][15] Du sek et al reported that the nodular structure is not an inherent property of cured epoxy resins because (i) both SEM images of fracture surfaces and SAXS curves of cured epoxy resins did not differ in principle from those of amorphous PMMA and PSt and (ii) swollen epoxy resins in tetrahydrofuran (THF) did not lead to an increase in the SAXS intensity corresponding to the particle size of 10-100 nm. 2,13 Matyi et al reported that SAXS results for epoxy resins indicated the presence of an inhomogeneity that is not associated with the nodular structure but with voids having a size distribution range larger than 10-100 nm.…”
Section: Introductionmentioning
confidence: 99%
“…2,13 Matyi et al reported that SAXS results for epoxy resins indicated the presence of an inhomogeneity that is not associated with the nodular structure but with voids having a size distribution range larger than 10-100 nm. 14 Bai reported that SANS results for epoxy resins indicated the absence of inhomogeneity of the cross-links in the range of 3-40 nm. 15 Tapping-mode atomic force microscopy (AFM) observations have also been reported in order to understand the cross-link inhomogeneity of epoxy resins through investigation of the hard and soft phases of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence for a nonhomogeneous network structure has been cited from dynamic mechanical analysis, swelling behavior and small angle X-ray scattering. [31][32][33] This work provides further evidence as to the nonhomogeneity of cured epoxy-amine systems by monitoring the development of the nonhomogeneous network architecture through the early stages of cure up to the onset of vitrification.…”
Section: Introductionmentioning
confidence: 99%